Awareness of vaccine cold chain handlers about vaccine cold chain in district Etawah - Kumar, Shishir; Singh, Naresh Pal; Jain, Pankaj Kumar; Kumar, Sandip (International Journal Of Community Medicine And Public Health, 2020)
Background: Vaccine potency can be lost when exposed to non-recommended temperatures. Hence for the proper running of the universal immunization programme (UIP) factors like vaccine cold chain and vaccine management wants great focus and attention skills and knowledge of the vaccine cold chain handlers so for good implementation of UIP vaccine cold chain handlers are important. Methods: This was an observational cross-sectional study. Study duration was carried out from October 2017 to March 2018. All the 16 cold chain handlers of district Etawah were interviewed. Results: All 16 (100.0%) were male and 1 (6.3%), 2 (12.5%), 8 (50.0%) and 5 (31.3%) of the respondents were high schools, intermediate, graduate, and post-graduate respectively. It had been observed that the hundred percent of the cold chain handlers with the knowledge of vaccine cold chain. It has been observed from the study that 15 (93.7%) cold chain handlers had knowledge of temperature range for vaccine storage. Conclusions: Quality of immunization program depends upon cold chain management at peripheral health institutions. In our study, we have found that most of the vaccine handlers were reported to have appropriate knowledge regarding the cold chain.